Pattern and predictors of immunologic recovery in human immunodeficiency virus-infected children receiving non-nucleoside reverse transcriptase inhibitor-based highly active antiretroviral therapy - Thanyawee Puthanakit (2018)
BACKGROUND: Non-nucleoside reverse transcription inhibitor (NNRTI)-based highly active antiretroviral therapy (HAART) is the recommended first-line regimen for children in Thailand. This study was aimed to assess pattern and predictors of immune recovery in antiretroviral-naive Thai children starting NNRTI-based HAART. METHODS: Records were extracted from clinical databases of 2 treatment cohorts in Thailand. The inclusion criteria were HIV-infected naive children who initiated NNRTI-based HAART when CD4 <25%. Immune recovery was defined as achieving a target CD4% of 25. The impact of age, gender, baseline clinical category, CD4 and HIV RNA titer, and regimen on immune recovery to weeks 96 was assessed using multiple logistic regression. RESULTS: There were 274 patients (52% females) with a median baseline age of 7 (Interquartile range [IQR]: 4-9) years and a median CD4% of 5 (IQR: 1-12) who started treatment with nevirapine (66%) or efavirenz (34%) based HAART. Median duration of follow-up was 168 (IQR: 120-192) weeks. The median CD4% increase from baseline was 7% (IQR: 5-11) and 18% (IQR: 12-23) at weeks 24 and 96, respectively. The probability of reaching target CD4% was 51% (95% confidence interval: 45%-57%) by week 96. The predictors of immune recovery at week 96 were younger age, female gender, higher baseline CD4%, and sustained virologic suppression after week 24. CONCLUSION: In this cohort of children with low baseline CD4, half achieved immune recovery after 96 weeks of HAART. The predictors for immune recovery are younger children, female gender, high baseline CD4%, and long-term virologic suppression. © 2009 by Lippincott Williams & Wilkins.